Mechanical activation of Hippo/TGFb pathways lead human saphenous vein progenitors toward pro-fibrotic differentiation in aorto-coronary bypass failure. (10th June 2022) - Garoffolo, G; Cassanmagnago, GC; Thomas, AT; De Vries, MDV; Ruiter, MSR; Carrara, MC; Vono, RV; Saccu, CS; Agrifoglio, MA; Martelli, FM; Condorelli, GC; Madeddu, PM; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ricerca Corrente Introduction: We previously demonstrated that mechanical stress deriving from coronary flow/pressure patterns in the human saphenous vein (SV) conduits induce release of Thrombospondin-1 (TSP-1) by smooth muscle cells, and this activates adventitial progenitors (SVPs) pathologic activation. Purpose: In this study, we show a cooperation of the TGF-β/TSP-1 signaling with the mechanically-activated Hippo transcriptional pathway in fibrotic SVPs commitment. Methods: Human derived-SVPs were isolated using a MACS based protocol with a positive selection for CD34 and a negative depletion of CD31+ cells. We performed an RNA-seq analysis of SVPs subjected to 10% uniaxial deformation (n=5), followed by differential gene expression and pathway analyses. We validated results in vitro and in two animal models of vein arterialization. Results: A response of SVPs to mechanical stimulation was assessed from variations in cell alignment, circularity and area. The susceptibility of SVPs to uniaxial strain was revealed by a trend of the cells to orientate in orthogonal direction to the strain field and changes in cell shape. Mechanically stimulated cells for 72 hrs showed a significant increase in their motility as verified by migration assays in the presence of medium supplemented with 10% serum. RNA-seq analysis of the total transcriptome expressed in these cells with/without mechanical stimulation was performed. The differentially expressed genes (DEGs) analysis highlighted a maximum variation of the transcriptome at 72hrs of mechanical stimulation vs. static controls with n=819 DEGs. A gene enrichment analysis revealed an involvement of the HIPPO/YAP/TEAD and of the TGF-β/SMAD transcriptional circuitries in mechanically-stimulated cells. In keeping, immunofluorescence and RT-qPCR showed an increase in YAP nuclear translocation and activity. We treated cells with a cytoskeleton inhibitor (Forskolin, FRSK) and a drug (Verteporfin, VTP) that prevents the interaction of the YAP/TAZ complex with TEADs. Both drugs inhibited expression of YAP-transcriptional targets and cellular motility in response to serum. We then treated cells with TGF-β1, TSP-1 alone or in combination. Under these conditions we observed an increased expression of YAP targets and CollA1, a higher amount of Collagen secretion in the supernatant and a higher association of YAP with pSMAD3. All these effects were blunted by VTP. YAP nuclear localization was finally validated in two models of vein arterialization in mice and pigs. Conclusions: Our data suggest a convergent activation of Hippo/TGF-β pathways in the failure of the aorto-coronary bypass and highlight a future novel strategy to limit its progression in patients.